PENERAPAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IVD SD NEGERI 163 PEKANBARU - Sri Intan Andriani; Syahrilfuddin Syahrilfuddin; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: Focused problem on this research is the low result of students achievement of mathematics learning. This is affected by convension learning method applied by teacher. Mathematic learning process only explain the subject without interact to student to solve the problem on math it self and not making math problem as real life acitivity. Beside the less active student and less chance for student to deliver his opinions. Its resulted on the student that easier to forget the explanation of the subject that they have learn. As the problem on student math result need to research applicable PMRI approach.Research of Classroom Action Research (CAR) with the goal of improving student learning result for IVD grade of SDN 163 Pekanbaru. Research conducted on 3 cycle. Each cycle consist of twice meetings and atthe end of each cycle repeated daily. Research data taken from observation teacher activity and students activity while learning and result of test at the end of the cycle.Average students learning result mathematic score was 53.11, onthe first cycleaverage score increase to21.4 became 74.51, on thesecond cycleincreaseinto 9.06 became 83.57, on the third cycle increase 3.48 became 87.05.Total increasing from basic score to UH 3 is 63,90%. Mastery learning of students on basis of a score is 23,68%, on the cycle I daily test passed percentage is 71,42%, in the daily test on second cycle passed percentagre is II is 84,21%, and in the daily test on cycle III is 89,47%. On the other side teacher activity on cycle I is 66.66% by category is good. The cycle IIis 77.77% by category is good and the cycle III is 88,89% by category is very good categorized. In the student activity percentage in first cycle was 59,71% by category was enough , in the second cycle 74,99% by category was good and the third cycle 86,10% by category was very good. Based on the research we can conclude that PMRI approaching can increase the result of mathematic subject for student at IVD grade SD Negeri 163 PekanbaruKeyword : Application of PMRI, Math Learning ResultWisuda Oktober